Пьесы - Булгаков Михаил Афанасьевич; Булгаков Михаил Афанасьевич (1990)
Экземпляры: ф.10 (1991) / Инвентарный номер: 22536 / Цена: 6.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Б 90 / ГРНТИ: 17.82.20 / ББК: 84(2Рос=Рус)6